微分方程$y' = 2y$的解为
A: $ e^{2x} $
B: $ Ce^{2x} $
C: $ e^{-2x} $
D: $ Ce^{-2x} $
A: $ e^{2x} $
B: $ Ce^{2x} $
C: $ e^{-2x} $
D: $ Ce^{-2x} $
举一反三
- 函数\( y = {e^x} \)是微分方程\( y'{e^{ - x}} + {y^2} - 2y{e^x} = 1 - {e^{2x}} \)的解。
- 已知\( y = {e^{2x}} \),则\( y' \)为( ). A: \( {e^x} \) B: \( 2{e^x} \) C: \( {e^{2x}} \) D: \( 2{e^{2x}} \)
- 微分方程$y' = 2y$的解为 A: $ e^{2x} $ B: $ Ce^{2x} $ C: $ e^{-2x} $ D: $ Ce^{-2x} $
- 已知\( y = {x^2} + 2x \),则\( y' \)为( ). A: \( 2x + 2 \) B: \( 2x \) C: \( 0 \) D: \( x \)
- 设\(z = u{e^v}\),\(u = {x^2} + {y^2}\),\(v = xy\),则\( { { \partial z} \over {\partial x}}=\) A: \({e^{xy}}({x^2}y + {y^3} + 2x)\) B: \({e^{xy}}({x}y^2 + {y^3} + 2x)\) C: \({e^{xy}}({x}y + {y^3} + 2x)\) D: \({e^{xy}}({x^2}y + {y^2} + 2x)\)